Arabic: short history, field of usage, and vocabulary entered in the Indonesian language - Sudaryanto Sudaryanto (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This essay discusses three fundamental issues about the Arabic language, which is (1) a brief history of the entry of Arabic to the Archipelago, (2) the field of use of the Arabic language, and (3) Arabic vocabulary that goes into Indonesian. At the end of the 15th Century AD, estimated Arabic brought by Arab traders, both derived from Hadramaut and of Persia. The use of Arabic in the field of Indonesian mostly related to religious life (Islam). As for the Arabic vocabulary that goes into Indonesian, among others, akhlak, amal, azab, akhirat, ayat, ilmu, ibadah, infak, insyaf, iman, imam, khilaf, khotbah, kitab, kalam, zaman, dan zina.